Datums and map projections for remote sensing, GIS, and surveying - Iliffe, Jonathan; Lott, Roger (Whittles Publishing, 2008)
A practical guide to coordinate reference systems, this book has become a key book for many students and professionals around the world. While retaining the benefits of the first edition - clear presentation assuming no prior knowledge, a problem-solving approach, practical examples and the combination of GPS-derived data from other sources - the rewritten and expanded second edition includes a revised structure that better groups common themes, greater scope and coverage of all possible types of coordinate reference systems, more examples and case studies from around the world, terminology of the ISO 1911, and color illustrations. --